A produção de subjetividade nos jogos eletrônicos - Lima, Leonardo Souza de (2011)
The present investigation explores the question of meaning production in video games, taking as foundation the subjectives conditions envolved in the relationship/interaction between player and game, within the scientific and academic literature environment. Part of the current discussion about the theoretical foundation of video games in general, which are postulated as a special category of objects in a transdisciplinary culture of constant transformation. It features electronic games (games) within a particular category of sensitive and reagents objects that participate in the constitution of a subjectivity in the context of the digital universe, which necessarily involves the relationship between human and non-human intelligence. Addresses this relationship from a multiple look, inter and transdisciplinary taking in count the socio-cultural, technological and semiotic aspects, which are formed in the context of discussing the status of the subject, object and world considered in the realm of the world and digital life. Incorporates elements of the discussion of post-structuralist philosophy, articulating an understanding of the concept of machinic subjectivity with the thematic aspects of the critique of representation, proposing to think video games in a structure coupled with the cognitive and sensitive faculties of human subject, that from his constitution as a system of signs of a-significant potential. From the nature of the particular object of study, this research develops the initial proposal for a qualitative and theoretical strategy, situating it in an exploratory examination of secondary data, direct observation via formal analysis of works and the production and documentation of a digital prototype game that explores the modes of relationship between the subject of the game, their avatars and the terms of playability, located from the conception of a academic and exploratory game. It culminates with the production and experimentation of a model that is heading toward a clearer idea of language devices operating in the construction of meaning in gaming, providing a contribution to increasing capacity for analysis and production of electronic games